Synthesis and properties of zinc-aluminium-acetylsalicylate-nanocomposite - Yahaya, Asmah; Hussein, Mohd Zobir; Zainal, Zulkarnain; Mamat, Mazidah (Universiti Putra Malaysia Press, 2005)
Intercalation of acetylsalicylate anion into zinc-aluminium-layered double hydroxide has been successfully accomplished via co-precipitation method. Good crystallinity of both the zinc-aluminium-layered double hydroxide (ZANO) and the zinc-aluminium-acetylsalicylate-nanocomposite (ZAAS) were obtained when the Zn/Al ratio used was 3. Expansion of the basal spacing of the layered double hydroxide (LDH) after intercalation process from 8.9 Å to 16.3 Å was observed. However, FTIR analysis showed that nitrate anion was co-intercalated into the interlayer of the nanocomposite and the result was in agreement with the elemental analysis. TGA-DTG results showed that the encapsulation of the acetylsalicylate anion into the interlayer increased its thermal stability. The nitrogen adsorption-desorption isotherms showed that the resulting materials were of Type IV with H3 hysteresis loop. SEM micrograph of ZANO showed its flaky-like structure; while that of ZAAS showed a compact structure.